Patients with psoriatic arthritis who are not eligible for randomised controlled trials for TNF inhibitors have treatment response and drug survival similar to those who are eligible - Palsson, Olafur; Love, Thorvardur Jon; Gunnarsdottir, Anna Ingibjorg; Gunnarsson, Petur Sigurdur; Runarsdottir, Eydis Erla; Krogh, Niels Steen; Gudbjornsson, Bjorn (RMD Open, 2019)
Objectives To determine in a retrospective cohort whether patients with psoriatic arthritis (PsA) who would not have fulfilled the inclusion criteria for randomised controlled trials (RCTs) for the TNF inhibitor (TNFi) chosen for their treatment (excl) have similar benefits and drug survival as those patients who would have (incl). Methods All patients with rheumatic disorders who are treated with biological disease-modifying antirheumatic drugs in Iceland are registered in ICEBIO. On 1 February 2016, 329 individuals with PsA were registered in ICEBIO, of whom 231 had data available for their first start of TNFi and could be evaluated according to the inclusion criteria of the respective RCTs. Disease activity was collected at baseline using Visual Analogue Scale (pain, fatigue and global (patient and physician) assessments), swollen joint count (SJC) and tender joint count (TJC), Disease Activity Score 28-joint count C reactive protein (DAS28-CRP) and Health Assessment Questionnaire (HAQ). Treatment response was measured at 6 and 18 months according to American College of Rheumatology response criteria, DAS28-CRP and Disease Activity Score in Psoriatic Arthritis for 28 joints. Drug survival rate was also analysed. Results The demographics of these two groups were similar at baseline, although the incl group had higher SJC (5.5 vs 3.8) and subsequently higher DAS28-CRP (4.6 vs 4.2). While a larger change in disease activity was observed in the incl group with respect to HAQ and SJC, both groups had similar disease activity at follow-up. Drug survival was similar in both groups. Conclusions Patients with PsA who would not have fulfilled the inclusion criteria in RCTs reach similar disease activity scores at follow-up of 6 and 18 months and have similar drug survival as those patients who would have been included in RCTs.